Decoupled effects of bone mass, microarchitecture and tissue property on the mechanical deterioration of osteoporotic bones. (15th November 2019) - Liu, Pan; Liang, Xiaoxiao; Li, Zhenzi; Zhu, Xiaobin; Zhang, Zuoqi; Cai, Lin
Abstract: Based on the theory of composite mechanics, a three-pillar framework "bone mass-microarchitecture-tissue property" instead of "bone mass-bone quality", is proposed to quantitively characterize the mechanical deterioration of osteoporotic cancellous bones related to the three aspects, and accordingly the individual and integrative influences of bone mass, microarchitecture and tissue property on the mechanical properties of cancellous bones are investigated via the μCT-based finite element method (FEM) simulations of bone samples from healthy and ovariectomy-induced osteoporosis mice. Comparisons among the healthy, mild osteoporotic and severe osteoporotic bones clearly show that the healthy bones have a larger bone volume density and an optimized architecture exhibiting longitudinal superiority able to more efficiently resist the daily loadings which are commonly along their longitudinal direction, while osteoporosis does not only significantly reduce the bone volume density but also greatly deteriorate the microarchitectural topology, resulting in a distinct reduction in the magnitude of effective Young's moduli and a breakdown of the longitudinal superiority as well. Furthermore, through modeling in silico we decoupled the three major factors to probe into their individual effects on the mechanical deterioration of osteoporotic bones. It was found that sole bone loss would exponentially decrease the effective Young's moduli of cancellous bones, microarchitecture plays a dominant role in defining the anisotropic characteristics of bones such as the longitudinal superiority; and change of tissue property seems having a slight and linear influence on the effective Young's moduli of cancellous bones.